Species composition and external morphology of echinoderms in Bintulu waters of exclusive economic zone (EEZ) Sarawak, South China Sea - Nur Farhani, Ahmad Muzeni (Universiti Malaysia Sarawak, (UNIMAS), 2016)
Echinodermata is a phylum that belongs to benthic invertebrates which has spiny skin. Presence of echinoderms community is important part in aquatic ecosystem in biological assessment as primary and secondary consumers. However, the information of this phylum is still poor in Malaysia especially in EEZ Sarawak waters. Hence, this study wanted to determine the variety of echinoderms specimens that had been obtained as part of bycatch from the M. V. SEAFDEC 2 survey using bottom otter trawl from 19 August until 2 September 2015. The aim of this study were (1) to document the species composition of echinoderms of South China Sea at the Exclusive Economic Zone Bintulu Sarawak waters according to depth strata strata (0-50 m, 51 - 100m and 100-200 m) and seabed type and (2) to describe the external morphology of the echinoderms. Samples were available at twenty stations out of 30 stations. Only four classes, ten orders and 13 families found in this study. Total of 21 species of echinoderms had been found. Most dominant class was Asteroidea and most dominant species was Ste/laster chi/dreni. Abnormality had been found on starfishes, S. childreni and Goniodiscaster scaber. There were eight species with new record in Malaysia waters. The most abundance at strata 0- 50 in and seabed mud, sand and shell. Total of 11 species at mud and sand seabed.